(untitled) (International Journal of Advanced Research in Science, Management and Technology, 2021)
Presently the automobile manufacturers are facing challenges of improvements in the quality and performance of the components together with the reduction in weight and cost of manufacturing. Efforts are directed towards the use of alternative materials in design which results in increase of strength to weight ratio. The use of composite materials is increasing in the design of automobile components due to their light weight and costs. The present work attempts to study the feasibility of select composite materials in the design of helical compression spring used in automobile suspension systems. The design of helical compression spring is first analyzed for the conventional steel material and then compared with that of for the composites used as spring materials study their behaviors at the different loading conditions. Composite materials considered for the analysis are Eglasss/Epoxy and Carbon/Epoxy. The modeling of the helical spring has been done using software and simulation were performed using ANSYS to predict the stresses, deflections at the stated loads. It was found that the stresses developed in conventional steel helical compression spring is more as compared to the stresses developed in composite material helical compression spring. Also the deflection is observed to be higher for composite materials. The results indicate that composite materials are feasible option at normal loading conditions which will also reduce the manufacturing and maintenance costs